1992
DOI: 10.1002/adma.19920040910
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a kinetically prohibited mesophase of a linear polymer into an enantiotropic mesophase via cyclization

Abstract: MATERIALS(0.29g, estimated 0.96mmol of Br based on the molecular formula [C,,H,,Br].), copper(]) iodide (0.04 mmol, 4.0 mol.-%), and dichlorobis-(triphenylphosphine)palladium(n) or tetrakis(triphenylphosphine)palladium(o) (0.05 mmol, 4.8 mol.-%) in THF (3 ml) was added at room temperature a terminal acetylene (2.9 mmol, 3.5 eq) and diisopropykdmine (2.9 mmol, 3.5 eq). The black reaction solution was stirred at room temperature for 1 h then warmed to 60 "C for 10 h and 100 "C for 5 h. The reaction mixture was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…We synthesized a new triblock copolymer with a large central block composed of the main-chain nematic polymer [10] that has been extensively used in studies of nematic elastomers and demonstrated very large shape-memory effect. [4,11] The large shape change in the main-chain polymer is due to the highly anisotropic conformation it acquires in the nematic phase, with the chain folded into hairpins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We synthesized a new triblock copolymer with a large central block composed of the main-chain nematic polymer [10] that has been extensively used in studies of nematic elastomers and demonstrated very large shape-memory effect. [4,11] The large shape change in the main-chain polymer is due to the highly anisotropic conformation it acquires in the nematic phase, with the chain folded into hairpins.…”
Section: Resultsmentioning
confidence: 99%
“…The startingmaterial1-(4-hydroxy-4′-biphenyl)-2-(4-hydroxyphenyl)butane, 1, was synthesized following the procedures of Percec and Kawasumi [10]. The a-(4-{1-[4′-(11-hydroxy undecanoxy)-biphenyl-4-ylmethyl]propyl}phenyl)-x- (11-hydroxy undecanoxy) poly[oxydecamethyleneoxy-4,4′-biphenyl-(2-ethylethylene-1,4-phenyl), (MCDIOL), was prepared using a modification of Finkelmann process [10,14], see Scheme 1.…”
Section: Preparation Of Triblock Copolymer 4ٞ-[a-(4-{1-[4′-(undecaneomentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of cyclic polymers studied by numerous research groups57–59, 62–66, 73, 74, 89, 95, 253, 268–289 comprised glass transition temperatures ( T g s), melting temperatures ( T m s), morphologies, melt viscosities, thermostabilities, and compatibilities. Cyclic PS, cyclic PEOs, and cyclic polysiloxanes were again the most widely studied cyclic polymers.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…[281][282][283][284][285][286][287] These cyclic oligoethers were prepared by phase-transfer-catalyzed polycondensations of a mesogenic but flexible diphenol with a,x-dibromoalkanes at low monomer concentration. Monodispers cyclic oligomers were isolated, and the influence of spacerlength and ring size on the temperature range of the nematic phase was studied.…”
Section: Bulk Propertiesmentioning
confidence: 99%